2020
DOI: 10.1136/vr.105682
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of Vibrio cholerae from fish examined postmortem at ZSL London Zoo between 2014 and 2018

Abstract: BackgroundWhen suspect Vibrio cholerae were cultured from fish at ZSL London Zoo, investigations were carried out to determine whether they were possible causes of cholera.MethodsBacterial culture was carried out on fish examined postmortem and colonies were identified using standard techniques including the API 20NE biochemical test kits. Suspect isolates were submitted to the Public Health England laboratory for additional testing. Separately, a number of fish were submitted for routine histopathology.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…These pathogens are plentiful in aquatic environments, where they are free-living in water or in association with aquatic fauna, considering opportunistic pathogens in many aquatic animals, such as marine fishes, crustaceans, and bivalves [11,12]. In addition, many Vibrio species have been implicated as causes of human foodborne illnesses as V. cholerae, V. parahaemolyticus, V. vulnificus, and V. alginolyticus are associated with gastroenteritis, severe dehydration, and primary septicemia due to the consumption of contaminated drinking water and undercooked or raw sea food [13,14]. Moreover, the relationship between Vibrio spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pathogens are plentiful in aquatic environments, where they are free-living in water or in association with aquatic fauna, considering opportunistic pathogens in many aquatic animals, such as marine fishes, crustaceans, and bivalves [11,12]. In addition, many Vibrio species have been implicated as causes of human foodborne illnesses as V. cholerae, V. parahaemolyticus, V. vulnificus, and V. alginolyticus are associated with gastroenteritis, severe dehydration, and primary septicemia due to the consumption of contaminated drinking water and undercooked or raw sea food [13,14]. Moreover, the relationship between Vibrio spp.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, fish have a mutualistic relationship with V. cholera as this bacterium secretes proteases and chitinases, with which they digest food (e.g., chitin and protein) in the fish gut [13,14,28]. Previous studies have reported the isolation of V. cholerae from the internal organs of diseased ayu (Plecoglossus altivelis) and guppy fish (Poecilia reticulate) in Japan and Iran, respectively [29][30][31], as well as from Nile tilapia (Oreochromis niloticus) that were cultured in floating cages in Thailand [32].…”
Section: Introductionmentioning
confidence: 99%